Endoscopic Transmaxillary orbitotomy for Cavernous Malformation: A Case Report with Technical Considerations - Haroon, Kaisar; Alam, Md Shafiul; Taher, Tania; Huq, Naila (Bangladesh Journal of Neurosurgery, 2022)
Cavernoma is a benign tumour of the orbit. It results in proptosis, visual disturbance, diplopia and ptosis of the eye. It is amenable to surgery without recurrence. We report a case of left orbital cavernoma in a female, who presented with non-pulsatile painless proptosis, without ptosis and no perception of light. Her MRI revealed a cavernoma of the left orbit inferior to the optic nerve. She was operated by the endoscopic transmaxillary orbitotomy. This easily removed the tumour, avoided craniotomy and was cosmetically acceptable. Bang. J Neurosurgery 2021; 11(1): 58-61